Development and Evaluation of a Rosacea Screening Instrument (Rosascreen). Issue 4 (July 2016) - Tan, Jerry; Leyden, James; Cribier, Bernard; Audibert, Fabien; Kerrouche, Nabil; Berg, Mats; ,
Background: There are no current instruments to facilitate population screening for rosacea. Objective: To develop and evaluate a screening instrument for rosacea applicable for population surveys. Methods: A rosacea-specific screening instrument (Rosascreen), consisting of a subject-completed questionnaire and screening algorithm, was developed based on current diagnostic criteria for rosacea. Three iterations were pilot tested and refined for clarity and sensitivity in adult outpatients with and without rosacea. Results: Three subject groups were consecutively evaluated with iterations of the questionnaire at each centre (overall N = 121). The final version had a sensitivity of 93% to 100% for key diagnostic criteria, and use of the algorithm had a sensitivity of 100% for detection of rosacea and specificity of 63% to 71%. Most subjects found the questionnaire easy to understand and complete. Conclusion: Rosascreen, a subject-completed questionnaire and diagnostic algorithm, is a highly sensitive screening instrument that may facilitate estimation of rosacea prevalence in general populations.